Enhancing EFL Thai Students’ Speaking Skill Through International Teaching Programs by Indonesia Preservice Teacher: A Classroom Action Design - Bayat, Putri; Erlindawaty, Erlindawaty (Universitas Pahlawan Tuanku Tambusai, 2025)
In the context of globalization, English speaking proficiency has become increasingly crucial, particularly in ASEAN countries such as Thailand. However, Thai EFL learners often struggle with speaking due to low confidence, limited vocabulary, and traditional teacher-centered methods. This Classroom Action Research (CAR) aimed to improve Thai primary students’ English-speaking skills through a culturally responsive and media-supported approach. The intervention was conducted at Islam Suksa Darulbir School, Satun, Thailand, during an international teaching program involving Indonesian preservice teachers from August 1–28, 2024. The program integrated YouTube video-based learning with interactive speaking activities across six sessions. The participants were 28 students from Grades V and VI with low speaking proficiency. Data were collected through speaking pre- and post-tests, classroom observations, interviews, and documentation. The results showed significant improvement in students’ accuracy (from 68.14 to 76.14), fluency (from 70.18 to 77.32), and comprehension (from 72.04 to 79.18), with an overall average gain of 7.54 points. Reliability testing using Cronbach’s Alpha yielded a value of 0.975, indicating excellent instrument consistency. Qualitative findings revealed increased classroom engagement, confidence, and communicative competence. Students responded enthusiastically to contextual video input and the culturally familiar presence of the Indonesian teacher, which fostered a supportive and interactive learning environment. The study concludes that integrating educational media with international teaching programs enhances speaking skills and learner motivation in EFL contexts. It recommends wider implementation of student-centered, media-rich strategies and expanded collaboration in cross-cultural teaching initiatives. These findings offer practical insights for educators, curriculum developers, and language policymakers aiming to improve EFL speaking instruction.